Application of step area algorithm in IDC traffic billing - Shizong LI; Zhihai CHEN; Yongming YAN (Dianxin kexue)
IDC customers reduce costs through traffic scheduling, which leads to waste of resources and increase of operation and maintenance costs of operators.Area billing could effectively improve this problem.It made a comparison between area billing and 95% peak rate billing method, and innovatively tried the step area algorithm.By connecting the difference between 95% peak rate value and average value and 95% peak rate billing and area billing price, the data dimension reduction was carried out, and the two-dimensional scatter diagram was obtained by programming exhaustive calculation, and the relationship between them was analyzed to explore the possibility of area billing.The experimental results show that the area of pricing could guide the customer does not adopt the way of traffic scheduling to reduce costs, in addition ladder area of billing way can meet the current traffic situation in the certain degree differ with 95 billing way smaller, the flow demand rises customers reduce costs, operators can get the corresponding profits at the same time, achieve a win-win situation.